Physical exercise and depression in adults and older adults - Pérez Bedoya, Édison Andrés (2024)
This thesis explores the effect of different physical exercise modalities on alleviating depressive symptoms in adults with major depressive disorder (MDD) and sedentary older women. The first study is a systematic review and meta-analysis of randomized controlled trials (RCTs) assessing the benefits and risks of physical exercise in managing symptoms of MDD in adults not receiving second-generation antidepressants or cognitive behavioral therapy. The review analyzed nine RCTs involving 678 adults, revealing a small, non-statistically significant clinical effect favoring exercise (SMD = 0.27, 95% CI [-0.58, 0.04], P = 0.09). Subgroup analyses indicated potential influences of intervention duration, frequency, intensity, supervision, age, overweight/obesity status, and depression diagnosis on treatment outcomes. Sensitivity analysis showed moderate effect sizes with high heterogeneity (I² = 85%), and overall evidence quality was low to very low. The second study is an RCT conducted at the Federal University of Viçosa, Brazil, comparing the effects of Flywheel resistance training versus traditional methods on depressive symptoms in 29 sedentary women over 60 years old. Participants underwent eight weeks of training, performing six exercises twice a week. Results indicated no significant difference between Flywheel and traditional training in reducing depressive symptoms (p=0.193), with a small effect size (ηp² = 0.03) and low statistical power (1-β = 0.25). Both interventions showed mild adverse events and no severe ones. In conclusion, both studies suggest that physical exercise, including resistance training, can benefit depressive symptoms, but further research with well-designed RCTs and larger sample sizes is needed to confirm these findings. The evidence underscores the importance of cautious interpretation due to methodological limitations and variability in results. Keywords: systematic review; meta-analysis; major depressive disorder; physical exercise; depression; elderly; exercise; resistance training; harms.